Polyiodide structures in thin single-walled carbon nanotubes: A large-scale density-functional study. (February 2019) - Rybkovskiy, D.V.; Impellizzeri, A.; Obraztsova, E.D.; Ewels, C.P.
Abstract: Using automatic structure generation algorithms and large-scale density functional computations we study polyiodide structures encapsulated within a 1 nm diameter single-walled carbon nanotube. The most energetically preferable confined iodine structures are the I3 −, I5 − and I8 2− molecular anions and periodic single, double and triple chain systems. The formation energy drops with increasing number of iodine atoms, reaching a minimum for a single iodine chain. Double and triple chains are metastable but have higher formation energies due to spatial confinement within the thin carbon nanotube. The calculated electron transfer from the nanotube to the molecular structures is close to the integer charge values of the molecular anions. The corresponding Fermi energy shift depends on the iodine concentration. For the single, double and triple chains the calculated Fermi shift is ∼0.13, ∼0.23 and ∼0.19 eV below the top of the nanotube valence band, respectively. The computational approaches presented here require minimal a priori knowledge of the system under study, yet are able to predict stable iodine structures observed in experiment. Graphical abstract: Image 1